127k views
4 votes
10q + 3q + 5 = 2 ( q - 3 )

User Mdundas
by
4.9k points

1 Answer

3 votes
Hi,

Work:

Equation;


10q + 3q + 5 = 2(q - 3)

Collect like terms.


13q + 5 = 2(q - 3)
Distribute 2 thought parenthesis.


13q + 5 = 2q - 6

Move variable 2q to left side and change its sign and move constant +5 to right side and change its sign.


13q - 2q = - 6 - 5
Collect like terms and calculate the difference.


11q = - 11
Divide both sides of equation by 11 and result is:


q = - 1


Hope this helps.
r3t40
User Max Brodin
by
6.0k points